2020
DOI: 10.12775/jehs.2020.10.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue and its proinflammatory properties

Abstract: For many years, adipose tissue was considered only as an energy store, additionally having an insulating and protective function against injuries. The discovery of the ob gene more than 20 years ago meant that adipose tissue is now seen as an endocrine gland regulating / modulating the body's energy metabolism, inflammatory and immune processes thanks to the secretion of bioactive molecules such as adipokines, enzymes, hormones and growth factors. The substances secreted by adipose tissue with a pro-inflammato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Adipose tissue plays a crucial role in signaling pathways that influence breast cancer development and progression. This depends not only from the adipose tissue mass but Interleukin-18 (ng/mL) also on breast adipocytes that surround breast tumor epithelial cells, which is the most abundant cell type in stroma of mammary gland [20].Among adipocytokines, adiponectin has a critical role in detecting breast cancer when it is elevated, especially in obesity-related cancers, including breast cancer. Many studies have demonstrated the relationship between hyperadiponectinemia and increased breast cancer risk, highlighting how patients with breast cancer who have higher adiponectin levels show a more aggressive phenotype [21].Direct evidence has been reported supporting the role of adiponectin as an inhibitory factor for breast cancer development and how it attenuates the growth of MDA-MB-231 cells by inhibiting cell proliferation and inducing apoptosis [22].…”
Section: The Mean Difference Is Significant At the 005 Level M: Malig...mentioning
confidence: 99%
“…Adipose tissue plays a crucial role in signaling pathways that influence breast cancer development and progression. This depends not only from the adipose tissue mass but Interleukin-18 (ng/mL) also on breast adipocytes that surround breast tumor epithelial cells, which is the most abundant cell type in stroma of mammary gland [20].Among adipocytokines, adiponectin has a critical role in detecting breast cancer when it is elevated, especially in obesity-related cancers, including breast cancer. Many studies have demonstrated the relationship between hyperadiponectinemia and increased breast cancer risk, highlighting how patients with breast cancer who have higher adiponectin levels show a more aggressive phenotype [21].Direct evidence has been reported supporting the role of adiponectin as an inhibitory factor for breast cancer development and how it attenuates the growth of MDA-MB-231 cells by inhibiting cell proliferation and inducing apoptosis [22].…”
Section: The Mean Difference Is Significant At the 005 Level M: Malig...mentioning
confidence: 99%